Wage Risk and the Value of Job Mobility in Early Employment Careers - Liu, Kai (Journal of Labor Economics, 2019)
This paper shows that job mobility is a valuable channel that employed workers use to mitigate bad labor market shocks. I estimate a model of wage dynamics jointly with a dynamic model of employment and job mobility. The key feature of the model is the specification of wage shocks at the worker-firm-match level, for workers can respond to these shocks by changing jobs. I find that, relative to the variance of individual-level shocks, the variance of match-level shocks is large and the consequent value of job mobility is substantial, particularly for workers whose match-specific wages are low.